Association of KLK4 rs2235091 polymorphism with susceptibility to dental caries: a systematic review and meta-analysis - Li, Youqin; Zhang, Lei; Cen, Wen; Yuan, Yongping (Frontiers in Pediatrics, 2023)
Objective: To investigate the association between Kallikrein-related peptidase-4 (KLK4) rs2235091 polymorphism and susceptibility to dental caries (DC) by a method of systematic review and meta-analysis.Methods: Four English databases were searched for studies on the correlation between KLK4 rs2235091 polymorphism and susceptibility to DC from inception to April 1, 2023. Data analysis was processed by Stata 15.0 software.Results: Four articles were eligible, including 848 individuals with caries and 463 controls. The results of pooled analysis showed no significant differences in the five gene models (G vs. A: odds ratio (OR) = 1.14, 95% CI: 0.73~1.79, P = 0.567; GG+GA vs. AA: OR= 1.01, 95%CI: 0.77~1.32, P= 0.489; GG vs. GA + AA: OR = 0.84, 95% CI: 0.57~1.23, P= 0.368; GA vs. AA: OR = 1.06, 95% CI: 0.80~1.41, P = 0.681; GG vs. AA: OR = 1.15, 95% CI: 0.57~2.31, P= 0.690). However, subgroup analysis indicated a statistically significant difference in the dominant (GG+GA vs. AA: OR= 1.74, 95%CI: 1.02~2.96, P= 0.042) gene model in primary dentition, but no significance in allelic, recessive, homozygous and heterozygous models. Besides, in permanent dentition, no significant differences were found among the five genetic models (all P ＞ 0.05). Conclusion: KLK4 rs2235091 polymorphism may be associated with susceptibility to DC of pediatric primary dentition, but not with the risk of caries of permanent dentition. Genotype GG+GA may increase susceptibility to DC of pediatric primary dentition. However, considering the limited records enrolled in this review, more trials with larger sample sizes and more rigorous designs are needed to verify the conclusions of this meta-analysis in the future.INPLASY registration number: INPLASY202380014.